2019
DOI: 10.33292/petier.v1i2.10
|View full text |Cite
|
Sign up to set email alerts
|

CIPP evaluation model for the coaching program of running athletes

Abstract: This study aimed to evaluate the training programs of sprinting, middle distance running, and long distance running athletes. This type of research is the study evaluation using CIPP models. The approach used in this study is a qualitative approach with qualitative data analysis model of Miles & Huberman. The results of the evaluation include: (1) context  evaluation shows that there are lack of budget, facilities, government’s support, sponsorship, health experts, test instrumens and test spaces, (2) eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 8 publications
2
19
0
2
Order By: Relevance
“…The activity of observing was in the form of watching a video. Thus, it can be concluded that the teacher followed the first step of the Scientific Approach that was in line with the statement of Nugraha dan Suherdi (2017) and Aldapit and Suharjana (2019).…”
Section: Processsupporting
confidence: 76%
“…The activity of observing was in the form of watching a video. Thus, it can be concluded that the teacher followed the first step of the Scientific Approach that was in line with the statement of Nugraha dan Suherdi (2017) and Aldapit and Suharjana (2019).…”
Section: Processsupporting
confidence: 76%
“…CIPP merupakan singkatan dari Context, Input, Process and Product. Evaluasi CIPP dikenal dengan nama evaluasi formatif dengan tujuan untuk mengambil keputusan dan perbaikan program (Aldapit & Suharjana, 2019;Hanifah & Irambona, 2019;Mulyatiningsih, 2011;Suryati & Haryanto, 2016).…”
Section: Metodeunclassified
“…Penelitian ini bertujuan untuk mengevaluasi penyelenggaraan sekolah lima hari di SMA Negeri 1 Ngemplak dengan menggunakan model evaluasi CIPP (Aldapit & Suharjana, 2019;Fitriyani & Robiasih, 2019;Sulistyawati & Guntur, 2019). Hasil penelitian ini memberikan gambaran tentang keterlaksanaan pendidikan karakter, pengembangan diri dan pembelajaran ketika diterapkannya sekolah selama lima hari.…”
Section: Hasil Dan Pembahasanunclassified